Community-Based Multiliteracy Assessment as a Strategy for Strengthening Inclusive Education (Lembaga Pengembangan Kinerja Dosen, 2025)
This research aims to explain how multiliteracy and community participation principles can be integrated into the assessment process to create a more inclusive learning space. Through a literature review approach, this article describes the conceptual framework and practical implications to be adopted in the context of induction education in higher education. The study's results, the first of which show that the multiliteracy approach opens up opportunities for learners to express their knowledge and understanding through various modalities. Second, community involvement in the assessment process through a community-based assessment model emphasizes the importance of the participation of multiple parties as partners in the observation and validation of learning outcomes. Third, the two can be integrated through participatory assessment strategies combining multiliteracy and democracy. This research recommends that learners and stakeholders design and implement assessments that value diversity, participation, and creativity.